A proposed decision-making model for evaluating a container's security score. (February 2014) - Riahi, Ramin; Li, Kevin; Robertson, Iain; Jenkinson, Ian; Bonsall, Steve; Wang, Jin
A container supply chain includes a large number of stakeholders who can physically come into contact with containers and their contents and are potentially related with the container trade and transportation. Security-based disruptions can occur at various points along the supply chain. Experience has shown that a limited percentage of inspection, coupled with a targeted approach based on risk analysis, can provide an acceptable security level. Thus, in order to not hamper the logistics process in an intolerable manner, the number of physical checks should be chosen cautiously. The aim of this article is to employ a set of data elements (i.e. an importer security filling, shipping documents, the value of an ocean or a sea carrier's reliability, the security scores of various commercial operators and their premises) to exploit a mathematical decision-making model for evaluating a container's security score. For evaluating a container's security score, a combination of different decision-making techniques such as Bayesian network and analytic hierarchy process is used. The methodology developed has been applied to a case study in order to demonstrate the process involved. Accordingly, the control options to avoid unnecessary delays and security scanning in dealing with containers are suggested.